Identification of a novel gene, H34, in wheat using recombinant inbred lines and single nucleotide polymorphism markers - Li, Chunlian; Chen, Ming-Shun; Chao, Shiaoman; Yu, Jianming; Bai, Guihua (My University, 2013)
Hessian fly (HF), Mayetiola destructor, is an important pest of wheat (Triticum aestivum L.) worldwide. Because it has multiple biotypes that are virulent to different wheat HF resistance genes, pyramiding multiple resistance genes in a cultivar can improve resistance durability, and finding DNA markers tightly linked to these genes is essential to this process. This study identified quantitative trait loci (QTLs) for Hessian fly resistance (HFR) in the wheat cultivar ‘Clark’ and tightly linked DNA markers for the QTLs. A linkage map was constructed with single nucleotide polymorphism and simple sequence repeat markers using a population of recombinant inbred lines (RILs) derived from the cross ‘Ning7840’ × ‘Clark’ by single-seed descent. Two QTLs associated with resistance to fly biotype GP were identified on chromosomes 6B and 1A, with the resistance alleles contributed from ‘Clark’. The QTL on 6B flanked by loci Xsnp921 and Xsnp2745 explained about 37.2 % of the phenotypic variation, and the QTL on 1A was flanked by Xgwm33 and Xsnp5150 and accounted for 13.3 % of phenotypic variation for HFR. The QTL on 6B has not been reported before and represents a novel wheat gene with resistance to HF, thus, it is designated H34. A significant positive epistasis was detected between the two QTLs that accounted for about 9.5 % of the mean phenotypic variation and increased HFR by 0.16. Our results indicated that different QTLs may contribute different degrees of resistance in a cultivar and that epistasis may play an important role in HFR.
Citation: Li, C., Chen, M., Chao, S. et al. Theor Appl Genet (2013) 126: 2065. https://doi.org/10.1007/s00122-013-2118-5
Keywords: Triticum aestivum; Hessian fly; Resistance gene; Quantitative trait loci; Single nucleotide polymorphism; Recombinant inbred lines